Beyond Ramsey: Gender-Based Taxation with Non-Cooperative Couples - Volker Meier; Helmut Rainer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper explores the implications of gender-based income taxation in a non-cooperative model of a couple's time allocation between market work and providing a household public good. We find that the optimal structure of differential taxation by gender is solely determined by spouses' relative marginal rates of substitution between the public household good and private consumption. Breaking down this general rule into the primitives of the model, the spouse with a lower personal valuation of the public household good should be taxed at a higher rate. If these valuations are identical, a comparative advantage in home production relative to market work will imply a higher marginal tax rate. Using a realistic calibration, we show that these two results may combine to imply a higher optimal tax rate on female labor supply. This result stands in sharp contrast to previous models of gender-based taxation in which households select Pareto efficient allocations. Extending the model to include altruistic preferences, leisure, or human capital accumulation reduces optimal tax rates, while sequential labor supply decisions affect the optimal tax rate of the primary earner in an ambiguous direction.
Keywords: H21; D13; J22; 330